Illustrated Discovery Learning Modules Facilitate Indonesian Vocabulary Mastery For Hearing Impaired Students: Modul Bergambar Discovery Learning Memfasilitasi Penguasaan Kosakata Indonesia Bagi Siswa Tunarungu - Nurhana Marian; Rendy Roos Handoyo (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Vocabulary mastery forms the essential foundation for linguistic comprehension, effective communication, and academic achievement within language education. Specific Background Fifth-grade students with severe hearing impairments at SDN 004 Teluk Pandan currently experience delayed language development and low assessment scores due to conventional, auditory-reliant instruction lacking appropriate visual media. Knowledge Gap While visually supported materials are generally beneficial, the specific integration of structured conceptual exploration frameworks combined with digital verification mechanisms for special needs literacy remains underexplored. Aims This study investigates the application of an illustrated instructional tool based on an active conceptual discovery framework to facilitate language acquisition for a hearing-impaired pupil. Results Utilizing Classroom Action Research across two instructional cycles, the analysis revealed a continuous score progression from a pre-cycle average of 65 to 89 in Cycle II, culminating in 100 percent classical proficiency. Novelty This research distinctly integrates structured visual exploration with QR Code-assisted digital verification to scaffold independent conceptual discovery without relying on auditory input. Implications Deploying highly visual, inquiry-oriented pedagogical materials provides a highly supportive alternative strategy for inclusive education, fostering learner autonomy, active classroom participation, and concrete semantic understanding. Highlights Classroom Action Research spanning two intervention cycles demonstrated a mean score progression from 65 to 89. Visual exploration and QR Code verification mechanisms successfully stimulated active participation within an inclusive educational setting. Tailored pedagogical interventions guided the participant to achieve complete classical proficiency standards. Keywords Visual Exploration Framework; QR Code Verification; Inclusive Education Strategies; Special Needs Pedagogy; Classroom Action Research